2021
DOI: 10.1016/j.jsams.2020.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Changes in exertion-related symptoms in adults and youth who have sustained a sport-related concussion

Abstract: Changes in exertion-related symptoms in adults and youth who have sustained a sport-related concussion. Rutschmann, Trevor Dean Rutschmann, T. D. (2018). Changes in exertion-related symptoms in adults and youth who have sustained a sport-related concussion (Unpublished master's thesis).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Rutschmann et al . 31 found immediate increases in symptom severity and number of symptoms, whereas Leddy et al . 26 found no impact on symptom severity within 48 h of testing.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Rutschmann et al . 31 found immediate increases in symptom severity and number of symptoms, whereas Leddy et al . 26 found no impact on symptom severity within 48 h of testing.…”
Section: Resultsmentioning
confidence: 92%
“…More evidence was available regarding the safety of implementation of the BCTT after a seven-day period following a concussion 8,12,31 and the findings consistently demonstrated no adverse responses to testing. It can therefore be concluded that the BCTT is safe to implement after a seven-day period.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations